Effects of balance transfer offers on consumer short-term finance: Evidence from credit card data - Yan Yuan; Toshiyuki Sueyoshi (Journal of Economic Structures, 2017)
This research investigates efficiency differences between two important financial approaches that credit card companies use to attract customers. Since the cash-back offer has been already investigated by previous studies, this study focuses upon the balance transfer offer and then compares them in terms of their influences on consumers' short-term finance. The proposed research utilizes the three-stage investigation. The first stage is related to consumers' choice on offers. The second stage estimates the offer's overall and monthly effects on payment, spending, and changes on debt in order to capture consumers' dynamic finance conditions. The last stage estimates the effects on balance transfer and cash-back offers compared with control and non-promotional finance conditions. This study finds that the balance transfer offer is more effective in making a financial impact to consumers' short-term finance than the cash-back offer.
Keywords: 330; Balance transfer; Short-term finance; Consumers' choices; Credit card